A fatal thaw - Stabenow, Dana (Stabenow, Dana. Kate Shugak series, 2023)
"Eleven days ago, Roger McAniff bought himself a new Winchester 30.06 rifle. Ten days ago he went out to test it. Now nine people are dead. But only eight were killed by McAniff... Stephen Syms. Patrick Jorgensen. Lyle and Lucy Longstaff. Lisa Getty. The Weiss family, John, Tina, and their two children. All slaughtered. Considering she would have been his final victim, private investigator Kate Shugak almost regrets not killing Roger McAniff. But Lisa Getty was killed by a different rifle. Different rifle, different shooter. And Kate is tasked with tracking this unknown killer down before the case goes completely cold..." -- Back cover.